2017
DOI: 10.1136/bmjopen-2017-016781
|View full text |Cite
|
Sign up to set email alerts
|

PATHway I: design and rationale for the investigation of the feasibility, clinical effectiveness and cost-effectiveness of a technology-enabled cardiac rehabilitation platform

Abstract: IntroductionExercise-based cardiac rehabilitation (CR) independently alters the clinical course of cardiovascular diseases resulting in a significant reduction in all-cause and cardiac mortality. However, only 15%–30% of all eligible patients participate in a phase 2 ambulatory programme. The uptake rate of community-based programmes following phase 2 CR and adherence to long-term exercise is extremely poor. Newer care models, involving telerehabilitation programmes that are delivered remotely, show considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…For example, the ongoing PATHway I trial, where the basis of the CR intervention is PA promotion and the primary outcome is objectively measured PA level. 39 …”
Section: Discussionmentioning
confidence: 99%
“…For example, the ongoing PATHway I trial, where the basis of the CR intervention is PA promotion and the primary outcome is objectively measured PA level. 39 …”
Section: Discussionmentioning
confidence: 99%
“…For further details on the intervention see Additional file 4 where the Template for Intervention Description and Replication (TIDieR) checklist is reported to ensure the completeness of reporting, and ultimately the replicability, of interventions [40]. For further details on validated tools/questionnaires used within the intervention please see the PATHway RCT protocol [41].…”
Section: Final Intervention Structure and Content Resulting From The mentioning
confidence: 99%
“…Patients participating in outpatient CR were invited during the last four weeks of outpatient CR to take part in the trial. Written informed consent was obtained and participants were then randomized to either the intervention group (PATHway) or the control group (usual care) [10]. A detailed description of the PATHway-I trial and quantitative results can be found elsewhere [10,13].…”
Section: Interventionmentioning
confidence: 99%
“…Written informed consent was obtained and participants were then randomized to either the intervention group (PATHway) or the control group (usual care) [10]. A detailed description of the PATHway-I trial and quantitative results can be found elsewhere [10,13]. In brief, one hundred and twenty participants were recruited across three sites in two countries: The Mater Misericordiae University Hospital (Dublin), Beaumont Hospital (Dublin) and University Hospital Leuven (UZ Leuven, Belgium).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation